2020
DOI: 10.1001/jamanetworkopen.2020.10986
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hearing Loss With Psychological Distress and Utilization of Mental Health Services Among Adults in the United States

Abstract: IMPORTANCE Psychological distress affects health and health care utilization. Hearing loss (HL) is highly prevalent and undertreated, and it may be a potentially modifiable risk factor for psychological distress. OBJECTIVE To investigate the association between HL, psychological distress, and mental health care utilization among adults in the United States. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study included 25 665 individuals aged 18 years and older who participated in the 2017 National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 52 publications
(96 reference statements)
0
28
0
3
Order By: Relevance
“…The effectiveness of HAs is rapidly improving with advances in modern technology (Arlinger & Billermark, 1999;Holube & Hamacher, 2005). In addition to assisting with communication difficulties, there is evidence to suggest that the use of HAs decreases depressive symptoms and social isolation (Bigelow et al, 2020;Cacciatore et al, 1999;Gopinath et al, 2012). Ongoing research is further investigating the reported positive influence of HA use on cognitive decline (Amieva et al, 2015;Deal et al, 2018;Sarant et al, 2019).…”
mentioning
confidence: 99%
“…The effectiveness of HAs is rapidly improving with advances in modern technology (Arlinger & Billermark, 1999;Holube & Hamacher, 2005). In addition to assisting with communication difficulties, there is evidence to suggest that the use of HAs decreases depressive symptoms and social isolation (Bigelow et al, 2020;Cacciatore et al, 1999;Gopinath et al, 2012). Ongoing research is further investigating the reported positive influence of HA use on cognitive decline (Amieva et al, 2015;Deal et al, 2018;Sarant et al, 2019).…”
mentioning
confidence: 99%
“…On the other hand, acute stress findings of hearing‐impaired individuals assessed via ASSS during the COVID‐19 pandemic were found to be higher compared to the control group. It has been previously shown that the use of the hearing aid has very significant positive effects on psychosocial lives and provide better quality of life 26 , 27 , which result in less distress. In our study, as we mentioned, we included only hearing‐impaired individuals using hearing aids.…”
Section: Discussionmentioning
confidence: 99%
“…While significant barriers and disparities in hearing health care and accessibility of care and services remain, as will be discussed later, the potential room for intervention growth and public health benefit is substantial. Management of hearing loss through amplification options may not only decrease risk for neuropsychiatric conditions ( Rutherford et al, 2018 ), but may also improve treatment adherence, patient satisfaction, and improve overall health-related quality of life for older adults ( Bigelow et al, 2020 ). Understanding subgroups of older adults who may receive particular benefit from increased amplification use may therefore save health care costs, reduce burden, and improve outcomes – including dementia.…”
Section: Epidemiology Of Hearing Lossmentioning
confidence: 99%